Study on Slagging Characteristics of Co-Combustion of Meager Coal and Spent Cathode Carbon Block - Jigang Zhang; Zijun Liu; Xian Li; Bin Wang; Zhaocai Teng; Kuihua Han (Energies, 2023)
The harmless disposal of spent cathode carbon blocks (SCCBs) has become an urgent issue in the primary aluminum industry, and the disposal of SCCBs by co-combustion in pulverized coal boilers is expected to be the most effective treatment method. A muffle furnace at 815 °C was used in this study to perform a co-combustion experiment of meager coal and SCCBs. The ash fusion characteristics (AFTs), microscopic morphology, and minerals composition of co-combustion ash were characterized. The interaction mechanism of different mineral components and the change in AFTs and viscosity-temperature characteristics were investigated using FactSage software. Results show that the change in the ash deformation temperature (DT) is correlated linearly with the SCCB addition ratio, whereas other characteristic temperatures exhibit a nonlinear relationship. The contents of SiO2, Al2O3, and Na2O collectively determine the DT in the ash, and the influence degree from high to low is in the order of SiO2, Na2O, and Al2O3. The phase diagram of Na2O–Al2O3–SiO2 is used to accurately predict the changing trend of the melting point of co-combustion ash. The ratio changes between refractory and fusible minerals in the ash, as well as the degree of low-temperature eutectic reaction between sodium- and calcium-containing minerals, are the main factors affecting the melting point of ash. When the blending amount of SCCBs is 5%, mostly complete combustion is achieved, and slagging does not occur easily. The optimal blending ratio of SCCBs is obtained using the co-combustion method from the aspect of AFTs and viscosity-temperature characteristics. This work lays a theoretical foundation for industrial application.